Motivations in political communications of national leaders in Singapore - Ong, Tricia Chui Hean (Nanyang Technological University, 2024)
The need for achievement (nAch), affiliation (nAff), power (nPow) are motives that energize and direct behavior and are modulated by behavioral restraints known as activity inhibition (AI). In political leadership, the leadership motive pattern is an established profile of an effective leader, consisting of high nPow, low nAff, and high AI. However, it is unclear if this motive pattern holds true for political leaders within Asia due to limited studies and mixing findings. This project seeks to examine the relationship of the three motives separately, nAch and nPow combined, and AI on the internal nation state through social welfare. To explore this, Singapore Prime Ministers’ National Day Rally speeches were analyzed for motive profile and AI and correlated with social welfare indicators. Overall, nPow and AI were negatively correlated with some social welfare indicators and the combined effect of nPow and nAch was positively correlated with some social welfare indicators. No significant correlations were observed between nAch or nAff and social welfare. Therefore, these findings suggest that the leadership motive pattern does not hold true for leader effectiveness measured in terms of social welfare in Singapore.